TI_GERICHTE 11.2015.89 vom 18. August 2017 , Cancellazione di una servitù per sopravvenuta mancanza d'interesse - TI Tribunale d'appello (2017)
Cancellazione di una servitù per sopravvenuta mancanza d'interesse